Type of Bone Graft or Substitute Does Not Affect Outcome of Spine Fusion With Instrumentation for Adolescent Idiopathic Scoliosis. Issue 17 (1st September 2015) - Theologis, Alexander A.; Tabaraee, Ehsan; Lin, Tracy; Lubicky, John; Diab, Mohammad
Abstract : Study Design: Retrospective cohort analysis. Objective: To compare clinical outcomes after spine instrumentation and fusion using 3 different bone grafts in children with adolescent idiopathic scoliosis (AIS). Summary of Background Data: Autogenous iliac crest bone graft (AIC) is the "gold standard" to promote fusion in posterior AIS operations, although the morbidity of harvest is a concern. There is limited data comparing outcomes after AIS surgery based on types of bone grafts. Methods: Children (10–18 yr) with AIS who underwent deformity correction via a posterior approach were identified in the Spinal Deformity Study Group database. All had a minimum of 2-year follow-up. Patients were subdivided into 3 groups based on bone graft used: AIC, allograft, and bone substitute (BS). Clinical data included patient demographics, operative details, postoperative analgesic use, and perioperative complications. Lenke curve type and curve magnitude changes were radiographically analyzed. The Scoliosis Research Society-30 questionnaire was used to assess clinical outcomes. Results: 461 patients met inclusion criteria (girls: 381, boys: 80; average age 14.7 ± 1.7) and consisted of 152 AIC patients (124 girls, 28 boys), 199 allograft patients (167 girls, 32 boys), and 110 BS patients (90 girls, 20 boys). There was no difference in age ( P = 0.41) or gender ( P = 0.82). The BS group had significantly smaller preoperative curves and shorter operative times. Postoperatively, patients who received BS had significantly longer hospital stays, used higher quantities of patient-controlled intravenous analgesia and used epidurals longer. The AIC group used patient-controlled intravenous analgesia significantly longer. There were no differences between the groups in regards to curve type, number of levels fused, postoperative infections, pseudarthrosis, reoperations for any indication, and Scoliosis Research Society-30 scores at the latest follow-up. Conclusion: Outcomes after primary posterior spinal fusion with instrumentation are not influenced by type of bone graft or substitute. Level of Evidence: 3 Abstract : In a retrospective analysis of 461 children with adolescent idiopathic scoliosis there were no differences in outcomes 2 years after primary posterior deformity correction on the basis of bone graft used (autogenous iliac crest vs. allograft vs. bone substitute).